The differences between legal and economic labor arbitrarion, and its impact on diffuse constitutional control - Acevedo Mercado, Jorge Luis (2014)
Labor Law is called to solve and prevent arisingconflicts between employers and employees. In light of this, certain conflicts between the employer and a union, or his own employees, can be solved by an arbitration board.In that line, it is important to take into account the many existing differences between juridical labor arbitration and economic labor arbitration; the author, in the present article, arguments that those differences represent the fundamental reason why the first one does exercise jurisdictional function and the second one does not. On that basis, the author affirms that it’s possible to exercise diffuse control in economic labor arbitration.